Experimental Evaluation of Brake Response Time on Motorcycle Brake Lamp - Azmi, Muhammad Akmal Izzat; Mustaffa, Norrizal (Journal of Automotive Powertrain and Transportation Technology, 2022)
Rear-end collisions are one of the highest contributors to road accidents fatalities, especially motorcycles which made up to 60% of the total of accidents that occur. The reasons that trigger such accidents are careless, dangerous turning (lane splitting and weaving between vehicles) and speeding, thus causing the awareness of the following vehicles to decline. That is why this study is conducted to find out the effectiveness of flashing brake lamps compared to conventional brake lamps on motorcycles. The experiment involves the driving experience, the distance between vehicles and gender as the factors that affect the brake response time (BRT) on brake lamps. The data collected are analysed and the findings showed that driving experience can influence the BRT, where experienced drivers have faster BRT (0.575 s) compared to others, however, beginner drivers demonstrate the highest BRT reduction by 13.4% (0.123 s). The analysis of the BRT based on the distance between vehicles displayed the driver’s adaptation to flashing brake lamps. The 10 m distance has the highest BRT reduction among other distances by 18.09% (0.142 s) even though the 6 m and 8 m distances presented a quite small BRT reduction, only around 0.04 s. Gender also illustrated the biggest impact of BRT on brake lamps, where males seem to be quicker to respond than females by 23.51% and 28.62% for conventional and flashing lamps respectively. As a whole, the flashing lamps portrayed shorter BRT than the conventional lamps by 9.87% (0.074 s). thus, it is suggested that flashing brake lamps is proven to reduce the BRT of the rear drivers and are suitable for implementation on motorcycles. Therefore, this study will benefit the future improvement and increase the conspicuity of motorcycle brake lamps.